Divine enticement : theological seductions - MacKendrick, Karmen, 1962- (Fordham University Press, 2012)
Theology usually appears to be dogmatic, judgmental, condescending, maybe therapeutic, or perhaps downright fantastical - but seldom enticing. This book takes as its starting point that the meanings of theological concepts are not so much logical, truth-valued propositions - affirmative or negative - as they are provocations and evocations. Thus it argues for the seductiveness of both theology and its subject - for, in fact, infinite seduction and enticement as the very sense of theological query. The divine name is one by which we are drawn toward the limits of thought, language, and flesh. The use of language in such conceptualization calls more than it designates. This is not a flaw or a result of vagueness or imprecision in theological language but rather marks the correspondence of such language to its subject: that which, outside of or at the limit of our thought, draws us as an enticement to desire, not least to intellectual desire. Central to the text is the strange semiotics of divine naming, as a call on that for which there cannot be a standard referent. The entanglement of sign and body, not least in interpretations of the Christian incarnation, both grounds and complicates the theological abstractions. A number of traditional notions in Christian theology are reconceived here as enticements, modes of drawing the desires of both body and mind: faith as "thinking with assent"; sacraments as "visible words" read in community; ethics as responsiveness to beauty; prayer as the language of address; scripture as the story of meaning-making. All of these culminate in a sense of a call to and from the purely possible, the open space into which we can be enticed, within which we can be divinely enticing.